PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA SDN 02 PURWOSARI KUDUS - Noor Aisyah; Wawan Shokib Rondli; Agus Darmuki (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The purpose of this study was to improve student learning outcomes in environmental materials through the use of problem-based learning (PBL) learning models. The type of research used is Classroom Action Research (PTK) which is carried out in II cycles. This research was conducted in three steps: (1) orienting students to the problem, (2) organising students to learn, and (3) analysing and evaluating the problem solving process. The research subjects were 14 second grade students of SD 2 Purwosari. The data collection technique was carried out by asking questions before and after the test regarding the content of interest. The results of the research are as follows a) At the initial meeting of the pre-cycle the percentage of student learning outcomes was 35 with an average score of 67.5. b) The completeness rate of cycle I was 64, an average of 74.5%. c) Cycle II the degree was 79 with an average score of 81.5. Based on the results of the research that has been done, the researcher can conclude that the problem-based learning (PBL) learning model is able to improve student learning outcomes in the material and environment that I am interested in.